Madam - Wynne, Phoebe (St. Martin's Press, an imprint of St. Martin's Publishing Group, 2021)
"A riveting, modern gothic debut with shades of The Secret History, The Stepford Wives, and a dash of Circe, set at a secretive all girls' boarding school perched on a craggy Scottish peninsula. For 150 years, high above rocky Scottish cliffs, Caldonbrae Hall has sat untouched, a beacon of excellence in an old ancestral castle. A boarding school for girls, it promises that the young women lucky enough to be admitted will emerge 'resilient and ready to serve society.' Into its illustrious midst steps Rose Christie: a 26-year-old Classics teacher, Caldonbrae's new head of the department, and the first hire for the school in over a decade. At first, Rose is overwhelmed to be invited into this institution, whose prestige is unrivaled. But she quickly discovers that behind the school's elitist veneer lies an impenetrable, starkly traditional culture that she struggles to reconcile with her modernist beliefs-not to mention her commitment to educating 'girls for the future.' It also doesn't take long for Rose to suspect that there's more to the secret circumstances surrounding the abrupt departure of her predecessor-a woman whose ghost lingers everywhere-than anyone is willing to let on. In her search for this mysterious former teacher, Rose instead uncovers the darkness that beats at the heart of Caldonbrae, forcing her to confront the true extent of the school's nefarious purpose, and her own role in perpetuating it. A darkly feminist tale pitched against a haunting backdrop, and populated by an electrifying cast of heroines, Madam will keep readers engrossed until the breathtaking conclusion"--